A Course module for teaching internship - Reyes, Ericson M.; Rivera, John Amiel A.; Sison, Trixie Marie J.; Pawilen, Greg Tabios (Manila : Rex Book Store, 2021)
This module is designed to serve as a teaching portfolio for student, teaching who are doing their teaching internship course or formerly known as practice teaching.
Chapter 1 : Preliminaries of teaching internship -- Chapter 2 : Preparing for classroom instruction -- Chapter 3 : Writing my daily reflective journal -- Chapter 4 : Documenting my teaching internship experience -- Chapter 5 : Preparing for the teaching profession.
Includes bibliographical references.
Keywords: STUDENT TEACHING; CLASSROOM MANAGEMENT